1994
DOI: 10.1002/jnr.490370408
|View full text |Cite
|
Sign up to set email alerts
|

Peptide bond specificity of calpain: Proteolysis of human myelin basic protein

Abstract: In order to determine the peptide bond specificity of calpain, human myelin basic protein (HMBP) was treated with purified calpain of bovine brain. Upon incubation, HMBP component I (HMBP-I) was degraded into several peptides as demonstrated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Component I was more susceptible to degradation than components II and III. HMBP degradation products were separated by high performance liquid chromatography (HPLC) and the cleavage sites in HMBP molecules were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…Calpains degrade neural proteins, including myelin proteins (i.e., MBP, PLP), and have long been thought to play a role in neurodegenerative processes (Siman et al, 1985;Sato et al, 1982;Chakrabarti and Banik, 1988;Yanagisawa et al, 1988;Tsubata and Takahashi, 1989;Banik et al, 1992Banik et al, , 1994. We have observed that partially purified calpain from lymphoid cells degrades purified MBP completely, and this degradation is both time-and calpain concentration-dependent.…”
Section: Discussionmentioning
confidence: 74%
“…Calpains degrade neural proteins, including myelin proteins (i.e., MBP, PLP), and have long been thought to play a role in neurodegenerative processes (Siman et al, 1985;Sato et al, 1982;Chakrabarti and Banik, 1988;Yanagisawa et al, 1988;Tsubata and Takahashi, 1989;Banik et al, 1992Banik et al, , 1994. We have observed that partially purified calpain from lymphoid cells degrades purified MBP completely, and this degradation is both time-and calpain concentration-dependent.…”
Section: Discussionmentioning
confidence: 74%
“…If calpain is secreted by activated microglia before or during symptomatic EAE, the extracellular calcium concentration would be sufficient to activate this proteinase at physiological pH. Because myelin proteins (including MBP) are calpain substrates used for EAE induction, we hypothesize that extracellular calpain may degrade myelin proteins to produce immunogenic fragments engulfed by antigen-presenting cells for major histocompatibility complex class II antigen presentation (26)(27)(28). A small percentage of activated mononuclear phagocytes, often observed in clusters in or adjacent to inflammatory foci, demonstrated large increases in calpain expression.…”
Section: Discussionmentioning
confidence: 99%
“…Several structural proteins such as neurofilament, spectrin, microtubule-associated protein, Tau and calcium channels act as substrates of calpains, which may be important for modification of neuronal morphology [92,99,100,112]. Alterations in intracellular Ca 2 + homeostasis and activation of calpains have been implicated in various neurodegenerative disorders [92,100,112,113]. Recently, Jordan et al [114] showed that calpains play a key role in b-amyloid-induced apoptosis of hippocampal neurons, which is blocked by overexpression of the Ca 2 + -binding protein calbindin D28K [115].…”
Section: Activation Of Pde1a2 By M-calpainmentioning
confidence: 99%
“…For example, protein kinase C, after cleavage by calpain, becomes fully active but no longer requires Ca 2 + and phospholipid for activation [111]. Several structural proteins such as neurofilament, spectrin, microtubule-associated protein, Tau and calcium channels act as substrates of calpains, which may be important for modification of neuronal morphology [92,99,100,112]. Alterations in intracellular Ca 2 + homeostasis and activation of calpains have been implicated in various neurodegenerative disorders [92,100,112,113].…”
Section: Activation Of Pde1a2 By M-calpainmentioning
confidence: 99%